SOTO ARANGO Diana, PANIAGUA Jesús, LIMA JARDILINO José Rubens, VERA DE FLASH María Cristina. (2011): Educadores latinoamericanos y del Caribe de la colonia a los siglos XIX y XX. Tomo III. Tunja, León, Sao Paulo, Córdoba. COLCIENCIAS, Universidad Pedagógica y Tecnológica de Colombia, DIN, RUDECOLOMBIA, Universidad de León España, Universidad Nove de Julho. Universidad Federal de Ouro Preto, Brasil, Universidad Nacional de Córdoba, Argentina, Universidad de Cuenca, Ecuador. Universidad de los Andes, Venezuela, Universidad de San Carlos de Guatemala, SHELAHISULA, 384 págs. ISBN: 978-958-660-178-8 - Uribe Angel, Jorge Tomás (2011)
No presenta resumen